Efeito da L-arginina e do BAY 73-6691 sobre as concentrações de TNF-α, IL-8 e óxido nítrico em neutrófilos de pacientes com anemia falciforme - Mota, Amanda de Menezes (2016)
Sickle cell anemia (SCA) is a hemoglobinopathy caused by a point mutation in the β-globin gene characterized by vaso-occlusive events and a chronic inflammatory state. Studies have demonstrated new treatment options in SCA in order to potentiate the action of Hydroxyurea (HU) and thereby promote decreased dosage without compromising fetal hemoglobin concentration, as well as the use of substances that may act in the inflammatory mechanism. The present study aimed to assess the effect of L-arginine and BAY 73-6691 on TNF-α concentration, IL-8 and nitric oxide in neutrophils from patients with sickle cell anemia. The study included 50 patients with a molecular diagnosis of SCA, treated at the hematology clinic at the University Hospital Walter Cantídio in Fortaleza, Ceará, and 30 healthy individuals as a control group. The patients were divided into two groups, according to the use of HU: SCAHU (30 patients treated with HU) and SCASS (20 patients not treated with HU). Neutrophils from patients were extracted from whole blood by density gradient difference and treated with L-arginine and BAY 73-6691 alone in the concentrations 0.1, 1, 10 and 100 ug / mL and L-arginine and BAY 73-6691 association at a concentration of 10 ug / ml. A group of untreated cells was used for comparison. Cytotoxicity was assessed by the LDH activity and MTT assay. TNF-α and IL-8 were determined by ELISA and NO levels by colorimetric assay. It has been observed that L-arginine and BAY 73-6691 isolated neutrophils caused toxicity in both groups only at the concentration of 100 ug / ml while the combination had no cytotoxic effects. L-arginine and BAY 73-6691 isolated and the combination were able to reduce levels of inflammatory markers TNF-α and IL-8 and to increase NO levels significantly in the SS group neutrophils in relation to the group untreated cells. The results of the study showed that L-arginine and BAY 73-6691 are potential therapeutic alternatives for SCA to be able to increase the bioavailability of NO and reducing the inflammatory process in neutrophils from patients with SCA not treated with HU.